Suboptimal complementary feeding practices as a driver of stunting: a risk factor analysis in children aged 12 -24 months - Maduka, Siti Wahyu Windarti; Febriawan, Zulfan (Sanus Medical Journal, 2025)
Introduction: Stunting has been a national problem in Indonesia. The prevalence of stunting in Bangkalan Regency was 26.2% based on the 2022 SSGI results. The government's target is to reduce the stunting rate to 14% by 2024. The WHO has set the global target for stunting prevalence below 20%. Inappropriate complementary feeding is one of the factors causing stunting in children. Aims: To determine the relationship between inappropriate complementary feeding and the incidence of stunting among children aged 12-24 months in Bangkalan Regency. Method: This research used an observational analytic, case-control design. A total of 12-to 24-month-old children were divided into two groups: a case group (stunting children) and a control group (normal children). The study was conducted from December 2024 to May 2025 at the Children's Outpatient Clinic of Anna Medika Madura Hospital. Statistical analysis using Chi-Square with a significance value of p<0.05. Results:  A total of 50 children in the case group and 50 in the control group. Boys were 59%, with an average age of 16.94 months. The results indicate the five parameters of complementary feeding, namely introduction of complementary feeding (p=0.003), feeding frequency (p=0.004), texture of complementary feeding (p=0.03), content of complementary feeding (p<0.001) and quantity of complementary feeding given (p=0.001) have a significant relationship in the case group with the incidence of stunting among children aged 12-24 months in Bangkalan Regency. Conclusion: There is a relationship between inappropriate complementary feeding and the incidence of stunting among children aged 12-24 months in Bangkalan Regency.   Pendahuluan: Stunting telah menjadi masalah nasional di Indonesia. Prevalensi stunting di Kabupaten Bangkalan adalah 26,2% berdasarkan hasil SSGI tahun 2022. Target pemerintah adalah mengurangi angka stunting menjadi 14% pada tahun 2024. WHO telah menetapkan target global untuk prevalensi stunting di bawah 20%. Pemberian makanan pendamping yang tidak tepat merupakan salah satu faktor penyebab stunting pada anak. Tujuan: Untuk mengetahui hubungan antara pemberian makanan pendamping yang tidak tepat dan kejadian stunting pada anak usia 12-24 bulan di Kabupaten Bangkalan. Metode: Penelitian ini merupakan penelitian observasional analitik dengan desain kasus kontrol. Sebanyak anak usia 12-24 bulan dibagi menjadi dua kelompok: kelompok kasus (anak stunting) dan kelompok kontrol (anak normal). Penelitian ini dilakukan dari Desember 2024 – Mei 2025 di Klinik Rawat Jalan Anak di Rumah Sakit Anna Medika Madura. Analisis statistik menggunakan Chi-Square dengan nilai signifikansi p<0,05. Hasil: Sebanyak 50 anak dalam kelompok kasus dan 50 anak dalam kelompok kontrol. Anak laki-laki berjumlah 59%, dengan usia rata-rata 16,94 bulan. Hasil penelitian menunjukkan lima parameter pemberian makanan pendamping, yaitu usia awal pemberian makanan pendamping (p=0,003), frekuensi pemberian makanan pendamping (p=0,004), tekstur makanan pendamping (p=0,03), kandungan makanan pendamping (p<0,001) dan jumlah makanan pendamping yang diberikan (p=0,001) memiliki hubungan yang signifikan pada kelompok kasus dengan kejadian stunting pada anak usia 12-24 bulan di Kabupaten Bangkalan. Kesimpulan: Terdapat hubungan antara pemberian makanan pendamping yang tidak tepat dan kejadian stunting pada anak usia 12-24 bulan di Kabupaten Bangkalan.